2001
DOI: 10.1046/j.1365-2540.2001.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the cleistogamous plant species Viola pubescens Aiton (Violaceae), as indicated by allozyme and ISSR molecular markers

Abstract: Few studies of genetic variation have focused on species that reproduce through both showy, chasmogamous (CH)¯owers and self-pollinated, cleistogamous (CL)¯owers. Using two dierent techniques, genetic variation was measured in six populations of Viola pubescens Aiton, a yellowowered violet found in the temperate forests of eastern North America. Results from eight allozyme loci showed that there was considerable genetic variation in the species, and population structuring was indicated by the presence of uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 39 publications
8
101
0
Order By: Relevance
“…However, it is important to notice that this technique may evaluate the polymorphism when f ingerprinting strategy is applied (Bornet and Branchard, 2001;Culley and Wolfe, 2001;Arnau et al, 2002). ISSR molecular markers appear as an excellent tool to study polymorphism in the four Fragaria groups included in this experiment.…”
Section: Analysis Of the Plants Genetic Diversitymentioning
confidence: 99%
“…However, it is important to notice that this technique may evaluate the polymorphism when f ingerprinting strategy is applied (Bornet and Branchard, 2001;Culley and Wolfe, 2001;Arnau et al, 2002). ISSR molecular markers appear as an excellent tool to study polymorphism in the four Fragaria groups included in this experiment.…”
Section: Analysis Of the Plants Genetic Diversitymentioning
confidence: 99%
“…Unfortunately, not all researchers collect vouchers during their work. For example, an allozyme analysis of a geographically distant Viola pubescens Aiton population indicated the unexpected presence of two distinct groups of genotypes ( Culley and Wolfe, 2001 ); unfortunately, vouchers had not been collected during the initial collecting trip, so the population had to be revisited before the different genotypes were confi rmed as two subspecies growing intermixed at the site.…”
Section: Vouchers Serve As a Tool For Identifying Locations Of A Taxonmentioning
confidence: 99%
“…It has been demonstrated that cleistogamy might influence the genetic structure of violets' populations. Genetic variation (measured by values of F ST or Θ indices) in Viola pubescens developing both CH and CL flowers was significantly higher (Culley and Wolfe, 2001) than in V. pedunculata with only CH flowers (Culley and Stokes, 2012). However, in V. striata and V. grahamii high population genetic diversity was maintained, despite very high frequency of CL flowers and vegetative reproduction (Cortes-Palomec et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…calaminaria, V. pubescens, V. riviniana, V. reichenbachiana, V. striata, V. grahamii, V. tricolor) differentiation among populations is weaker because it is balanced by the existing gene flow (Auge et al, 2001;Culley and Wolfe, 2001;CortesPalomec et al, 2006;Bizoux et al, 2008;Słomka et al, 2011;Kuta et al, 2014;Cánovas et al, 2015;Migdałek, 2015). The Mantel test performed on V. uliginosa populations revealed a significant correlation between genetic and geographical distances, showing, that gene flow vectors (pollination and diaspore dispersal) are weak even on such relatively short distances.…”
Section: Discussionmentioning
confidence: 99%